Experimental investigation on detonation dynamics through a reactivity sink - Boulal, Stéphane; Vidal, Pierre; Zitoun, Ratiba; Matsumoto, Takuya; Matsuo, Akiko (Combustion and flame, 2018)
This article reports on an experimental investigation into dynamical behaviours of detonation in non-uniform mixtures, generated from stoichiometric propane–oxygen, oxygen and ethane, with initial temperature and pressure 290 K and 20 kPa, respectively. Composition gradients are parallel to the direction of detonation propagation, with an equivalence ratio (ER) that first decreases from lean values and then increases to rich ones. Composition distributions are characterized according to the depth of the ER sink. Gradients are generated in a 50 × 50-mm2-square cross-section and a 665-mm total length chamber. The mixture components are injected separately in the pre-evacuated chamber in their order of decreasing density through porous plates at the chamber top-end to ensure planar filling of the chamber. Non-uniform distributions are then precisely controlled as a function of time by means of optical oxygen sensors. A Chapman–Jouguet (CJ) detonation is transmitted at the chamber bottom-end from a 3.6-m-long driver tube. Fast pressure transducers, sooted plates and Schlieren visualizations coupled with high-speed cameras are used to characterize the longitudinal velocity, cellular structure and transmission, failure and re-initiation mechanisms of the detonation front. Shallowest ER sinks produce the supercritical transmission mode of the CJ detonation with continuous adaptation of velocity and multicellular structure to local composition. Deepest sinks lead to the subcritical behaviour characterized by sudden detonation failure from shock-flame decoupling when ER decreases, and without detonation re-initiation when ER increases again. Intermediate sink depths generate critical behaviour with detonation re-initiat ion at chamber walls from expanding combustion kernels and reflected transverse Mach waves and then from SWACER retro-active mechanism. An elaboration of the failure criterion used in a previous study is found to well predict conditions for shock-flame decoupling.